A randomized controlled trial of acupressure as an adjunctive therapy to sodium valproate on the prevention of chronic migraine with aura. Issue 27 (July 2017) - Xu, Ji-hua; Mi, He-yin
Abstract: Background: The primary objective of the present study was to evaluate the efficacy and safety of using acupressure as an adjunctive therapy to sodium valproate (SV) combined with acupressure (ASV) on the prevention of chronic migraine with aura (CMA). Methods: A total of 98 patients with CMA were randomly divided into an intervention group and a control group, with 49 patients in each group. The patients in the intervention group received ASV, while the participants in the control group received SV alone. The primary outcome was measured by the numeric rating scale (NRS). The secondary outcomes including frequency of migraine attacks, the times of using analgesics, and quality of life, measured by the short-form 36 Health Survey Scale (SF-36) score. In addition, adverse events (AEs) were also recorded throughout the trial. The outcomes were measured at the end of the 8-week treatment, and 4-week follow-up. Results: After the 8-week treatment and 4-week follow-up, ASV efficacy was not greater than that of SV alone regarding pain relief, as measured using the NRS, and frequency of migraine attacks, consumption of analgesics, and quality of life, as measured using the SF-36. However, ASV can significantly reduce the nausea when compared with SV ( P  = .04). Conclusion: The present results indicate that ASV can decrease migraine-related nausea during treatment, but cannot relieve pain or enhance quality of life in patients with CMA.